Autoantigens: Novel forms and presentation to the immune system. (5th November 2013) - Doyle, Hester A.; Yang, Mei-Ling; Raycroft, Maurice T.; Gee, Renelle J.; Mamula, Mark J.
Abstract: It is clear that lupus autoimmunity is marked by a variety of abnormalities, including those found at a macroscopic scale, cells and tissues, as well as more microenvironmental influences, originating at the individual cell surface through to the nucleus. The convergence of genetic, epigenetic, and perhaps environmental influences all lead to the overt clinical expression of disease, reflected by the presences of autoantibodies and tissue pathology. This review will address several specific areas that fall among the non-genetic factors that contribute to lupus autoimmunity and related syndromes. In particular, we will discuss the importance of understanding various protein post-translational modifications (PTMs), mechanisms that mediate the ability of "modified self" to trigger autoimmunity, and how these PTMs influence lupus diagnosis. Finally, we will discuss altered pathways of autoantigen presentation that may contribute to the perpetuation of chronic autoimmune disease.